High quantum efficiency N-structure type-II superlattice mid-wavelength infrared detector with resonant cavity enhanced design. (May 2017) - Wu, Haoyue; Xu, Yun; Li, Jian; Jiang, Yu; Bai, Lin; Yu, Hailong; Fu, Dong; Zhu, Haijun; Song, Guofeng
Abstract: We propose a resonant cavity enhanced (RCE) N-structure type-II superlattice (T2SL) mid-wavelength infrared (MWIR) photodetector which can be used for the detection of methane gas at 3.3 μm. The theoretical analysis of quantum efficiency ( QE ) shows that the peak QE can be enhanced from 0.45 to 0.80 at 3.3 μm after 12 period AlAs0.09 Sb0.91 /GaSb DBR is introduced to the N-structure T2SL detector and QE exhibits the narrow bandwidth characteristic near the target wavelength. By analyzing the refractive indices of different materials and the reflectance of different DBRs, we also discuss how to determine the component materials of quarter-wavelength DBR reflectors. Highlights: Novel RCE N-structure MWIR T2SL photodetector is proposed. The peak QE can be enhanced from 0.45 to 0.80 at 3.3 μm after incorporating the AlAs0.09 Sb0.91 /GaSb DBR. QE exhibits the narrow bandwidth characteristic near the target wavelength according to the simulation results.